Thermomechanical treatments influence on the phase composition, microstructure, and selected mechanical properties of Ti–20Zr–Mo alloys system for biomedical applications - Kuroda, P. A.B. [UNESP]; Lourenço, M. L. [UNESP]; Correa, D. R.N.; Grandini, C. R. [UNESP] (Elsevier, 2020)
The study and development of new titanium alloys aim to place a metallic biomedical device with better mechanical compatibility with the bone, that is, with a smaller Young's modulus, on the market, to improve its application in the orthopedic and dental fields. This study analyzed the influence of thermomechanical treatments on the structure, hardness, and elastic modulus of the Ti–20Zr–Mo ternary alloy system, where the molybdenum content varied between 0 and 10 wt%. The treatments performed in this study involved homogenization, hot-rolling, and annealing. The structural and microstructural analyses were performed by X-ray diffraction, optical and scanning electron microscopy. An analysis of the mechanical properties of the alloy was obtained by measuring Vickers microhardness and the dynamic elastic modulus. The structural and microstructural results indicated that the Ti–20Zr alloy has only the α′ phase, the Ti–20Zr–10Mo alloy had a predominance of β phase, and the other alloys were α+β types. The hardness increased due to solid-state hardening with the increase of the molybdenum content and due to hot-rolling processing, which increased the internal stresses of the material. The elastic modulus decreased with higher levels of molybdenum and the hot-rolling processing, due to β phase stabilization. The other treatments increased the elastic modulus and may even induce the formation of the omega phase in some alloys of the system.
Keywords: Mechanical properties; Metallic biomaterial; Microstructure; Thermomechanical treatments; Ti alloys